From Spain to Carajá: Hispanism in "La Novela del Indio Tupinamba" by Eugenio F. Granell - Palomeque Recio, Azahara (Madrygal. Revista de Estudios Gallegos, 2015)
This article analyzes La Novela del Indio Tupinamba (1959) by the Galician writer Eugenio Granell, who was affiliated with the POUM party and exiled after the Spanish Civil War. The article takes into consideration his intervention into the field of cultural production (Bourdieu), starting with his critique of the “discursive imperialism” (Díaz Quiñones), called “hispanism”, which has traditionally characterized the relationship between Spain and its former colonies.
Keywords: Eugenio Granell; hispanism; imperialism; Spanish Civil War; exile